TINGKAT KEMAMPUAN BERPIKIR KRITIS SISWA DALAM MENYELESIKAN SOAL BARISAN DAN DERET ARITMATIKA DI SMAN 5 JEMBER - Rahmatillah, Siti; Hobri, Hobri; Oktavianingtyas, Ervin (Kadikma, 2017)
Abstract. Critical thinking ability is a Students’ thinking ability in solving questions based on some components of Paul’s and Elder’s critical thinking with indicators used in this research is reasoning element (information, concept, idea, conclusion, and point of view) and reasoning intellectual standard (clear, appropriate, careful, relevant, deep, logical, and wide). The purpose of this research is to describe students critical thinking ability in solving arithmetic sequence and series questions in SMAN 5 Jember. The subject of this research was taken from 29 students of X MIPA 4 were categorized into 3 groups which are high, medium, and low ability based on their mathematic scores in the first semester. Based on the result of the critical thinking ability test and the interview, two subjects which were taken from low ability students were categorized as TKBK 0 (not critical). Three subject which were taken from medium ability students, one subject was categorized as TKBK 1 (less critical) and two subjects were categorized TKBK 2 (critical enough). One subject which was taken from high ability students was categorized as TKBK 3 (critical). From the result of the research, the subject is only able to reach critical level (TKBK 3) and 5 of the other subjects are still in the low critical thinking level which are TKBK 2, TKBK 1 and TKBK 0. Keywords: Critical Thinking Ability Level, Arithmetic Sequence and Series, Students’ Beginning Ability